Investigation of municipal solid waste (MSW) and industrial landfills as a potential source of secondary raw materials - Coulon, Frederic; Wagland, Stuart T.; Griffiths, Zoe (Cranfield University, 2018)
in-depth characterisation of a number of selected municipal and industrial landfill pilot sites as well as mining disposal sites have been assessed for enhanced landfill mining opportunities
Keywords: Raw materials; landfill sites; Mining engineering; Rare Earth Elements Mine Mining activity; Environmental Science